Circulating MicroRNA markers for pulmonary hypertension in supervised exercise intervention and nightly oxygen intervention - Grunig, Gabriele; Eichstaedt, Christina; Grünig, Ekkehard (Frontiers in physiology, 2018)
Rationale: Therapeutic exercise training has been shown to significantly improve pulmonary hypertension (PH), including 6-minute walking distance and right heart function. Supplemental nightly oxygen also has therapeutic effects. A biomarker tool that could query critical gene networks would aid in understanding the molecular effects of the interventions. Methods: Paired bio-banked serum (n=31) or plasma (n=21) samples from the exercise or oxygen intervention studies, respectively, and bio-banked plasma samples (n=20) from high altitude induced PH in cattle were tested. MicroRNAs (miRNAs) markers were chosen for study because they regulate gene expression, control the function of specific gene networks, and are conserved across species. Results: MiRNAs that control muscle (miR-22-3p, miR-21-5p) or erythrocyte function (miR-451a) were chosen based on pilot experiments. Plasma samples from cattle that developed PH in high altitude had significantly higher miR-22-3p /(relative to) miR-451a values when compared to control cattle tolerant to high altitude. Measurements of miR-22-3p/miR-451a values in serum from patients receiving exercise training showed that the values were significantly decreased in 74.2% of the samples following intervention and significantly increased in the remainder (25.8%). In samples obtained after exercise intervention, a higher composite miRNA value, made of miR-22-3p and miR-21-5p / miR-451a and spike RNA, was significantly decreased in 65% of the samples and significantly increased in 35% of the samples. In the study of nightly oxygen intervention, when comparing placebo and oxygen, half of the samples showed a significant down-ward change and the other half a significant up-ward change measuring either of the miRNA markers. Samples that had a downward change in the miRNA marker following either intervention originated from patients who had a significantly higher 6-minute-walking-distance at baseline (mean difference of 90 m or 80 m following exercise or oxygen intervention, respectively) when compared to samples that had an upward change in the miRNA marker. Conclusions: These natural animal model and human sample studies further highlight the utility of miRNAs as future biomarkers. The different directional changes of the miRNA markers following supervised exercise training or nightly oxygen intervention could indicate different PAH molecular pathomechanisms (endotypes). Further studies are needed to test this idea
Gesehen am 21.05.2019